Mammograms from cancer screening - Dahlblom, Victor; Dustler, Magnus; Zackrisson, Sophia (AIDA Data Hub, 2019)
14711 digital mammography (DM) examinations from screening, usually including two projections (mediolateral oblique and craniocaudal) of each breast. Categorized cancer positive/negative. 95 cancer cases diagnosed on DM. Part of this dataset is directly available for inspection for partners on the AIDA platform, and the rest can be made available on request. This dataset is an anonymized excerpt from a dataset with richer associated data, collected in a research project which is still ongoing. The authors welcome proposals for new impactful research collaborations.
Keywords: Radiology; Breast; Cancer; Mammography; MMG; MG; MAMMO; DM; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi; Radiology and Medical Imaging; Radiologi och bildbehandling